2009
DOI: 10.1007/s00441-009-0833-7
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory papillae and taste bud development and maintenance in the absence of TrkB ligands BDNF and NT-4

Abstract: Taste buds and the peripheral nerves innervating them are two important components of the peripheral gustatory system. They require appropriate connections for the taste system to function. Neurotrophic factors play crucial roles in the innervation of peripheral sensory organs and tissues. Both brain-derived neurotrophic factor (BDNF) null-mutated and neurotrophin-4 (NT-4) null-mutated mice exhibit peripheral gustatory deficits. BDNF and NT-4 bind to a common high affinity tyrosine kinase receptor, TrkB (NTRK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…2010). Although immature taste buds are detectable in embryonic taste papillae by K8-ir (Ito and Nosrat, 2009;Thirumangalathu et al, 2009), most fungiform taste buds do not express markers of specific taste cell types until the first postnatal week (Kapsimali and Barlow, 2013). Previously, we found that activation of β-catenin in K14 + embryonic epithelium caused precocious differentiation of a small number of Type II taste cells .…”
Section: Resultsmentioning
confidence: 89%
“…2010). Although immature taste buds are detectable in embryonic taste papillae by K8-ir (Ito and Nosrat, 2009;Thirumangalathu et al, 2009), most fungiform taste buds do not express markers of specific taste cell types until the first postnatal week (Kapsimali and Barlow, 2013). Previously, we found that activation of β-catenin in K14 + embryonic epithelium caused precocious differentiation of a small number of Type II taste cells .…”
Section: Resultsmentioning
confidence: 89%
“…Several studies suggest that the initial stages of taste papillae development are nerveindependent (Fritzsch et al 1997;Barlow and Northcutt 1998;Ito and Nosrat 2009). However, poorly innervated papillae are distorted or malformed at late embryonic and early postnatal stages (Fritzsch et al 1997;Nosrat et al 1997;Zhang et al 1997;Nosrat et al 2004;Ito and Nosrat 2009). Therefore, we have focused on the initial stages of papillary formation, when the structure of papillae is not affected by innervation.…”
Section: Discussionmentioning
confidence: 98%
“…*Statistically significant difference at P<0.05 decreased nerve supply. Smaller and sparser fungiform papillae compared with the wild-type have been reported to occur in mice deficient in brain-derived neurotropic factor (BDNF) and neurotrophin (NT), viz., BDNF -/-NT-4 -/- (Ito and Nosrat 2009), in BDNF -/-NT-3 -/-mice (Nosrat et al 2004), and in mice deficient in neurotrophin receptor TrkB (TrkB -/-; Fritzsch et al 1997) with various degrees of geniculate ganglion cell loss.…”
Section: Discussionmentioning
confidence: 99%
“…Not all neurotrophin knockout and receptor mice lose the same number of taste buds; for example, TrkB −/− mice possess more taste buds than hybrid Bdnf −/− / Nt4 −/− mice at birth [15,17,58]. The reason for this is unclear but we speculated that the additional taste buds might be supported by BDNF or NT4 functioning via p75.…”
Section: Discussionmentioning
confidence: 99%